DESIGNING A STORY BOOK AS NARRATIVE READING MATERIALS BASED ON WEST KALIMANTAN FOLKTALES - Nugraha, Ibnu Sholaah; Ikhsanudin, Ikhsanudin; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of this research was to design a story book based on West Kalimantan folktales to support teaching reading narrative text. In this research, the method was developmental research that used ADDE instructional design as the phase in developing the materials.Â The story book is intended to be supplementary materials in teaching reading narrative text. The story book was assessed by the experts according to several aspects. Total score of the expert assessment of the content was 95.83% by the maximum score was 100% and total score of the expert assessment of the illustration design was 95.45% by the maximum score was 100%.The experts assessment result showed that the story book was suitable and in good quality to be used by the teacher and students as supplementary material to support teaching reading narrative text.Keywords: Local Folktales, ADDIE Approach, Reading MaterialsÂ Abstrak: Tujuan dari penelitian ini adalah untuk merancang sebuah buku cerita berdasarkan cerita daerah Kalimantan Barat untuk mendukung pengajaran membaca teks naratif. Metode yang di gunakan dalam penelitian ini adalah pengembangan materi yang menerapkan ADDE sebagai prosedur. Buku cerita di gunakan sebagai materi tambahan dalam mengajarkan membaca teks naratif. Buku cerita telah di nilai oleh dua orang ahli berdasarkan beberapa aspek. Nilai total dari penilaian ahli berdasarkan isi buku cerita adalah 95.83% dengan nilai maksimal 100% dan nilai total dari penilaian ahli berdasarkan bentuk ilustrasi adalah 95.45% dengan nilai maksimal 100%. Hasil dari penilaian ahli menunjukan bahwa buku cerita yang di buat oleh peneliti sesuai dan memiliki kualitas yang baik untuk digunakan oleh guru dan siswa sebagai materi tambahan untuk mendukung pengajaran membaca teks naratif.Kata kunci: Cerita Daerah, Pendekatan ADDIE, Materi Reading